Inclined Injection of Supersonic Steam into Subcooled Water A CFD Analysis - Afrasyab, Khan; Khairuddin, Sanaullah; M Sobri, Takriff; Hushairi, Zen; Lim, Soh Fong (Trans Tech Publications, 2014)
The phenomenon of direct-contact condensation gains attention because of various industrial applications; nuclear reactor emergency core cooling systems,steam driven jet injectors, direct-contact heat exchangers etc..The phenomenon was investigated computationally by injecting an inclined steam jet using a supersonic nozzle submerged in subcooled water. The condensation mechanism is based on two resistance model, which involves consideration of the heat transfer process on both sides of the interface along with use of a variable steam bubble diameter. For computations, ANSYS Fluent based Euler-Euler multiphase model is used. The angle of inclination varies from 5o to 45o at constant inlet pressure of 7 bars with water temperature of 30oC. The maximum penetration length is achieved using a right angled vertical injection.